A review of carbon dioxide sequestration by mineral carbonation of industrial byproduct gypsum. (15th June 2021) - Wang, Bo; Pan, Zihe; Cheng, Huaigang; Zhang, Zhien; Cheng, Fangqin
Abstract: Mineral carbonation to sequester carbon dioxide presents the potential for mitigating global warming. Currently, byproduct gypsum, an industrial solid waste, was used to fix carbon dioxide through mineral carbonation showing the great advantages due to its fast carbonation rate and high carbonation reactivity (above 95%). This process is a promising strategy to mitigate the environmental issue of byproduct gypsum stacking and the carbon dioxide concentration. In this review, the process of mineral carbonation of byproduct gypsum containing direct and indirect routes is discussed. Additionally, the carbonation kinetics and the synthesis of tunable calcium carbonate are elaborated. The economic analysis and environmental impact of the process are evaluated. Furthermore, the challenges and future work of mineral carbonation of byproduct gypsum for carbon dioxide storage are proposed. This review can provide guidelines for mineral carbonation of byproduct gypsum on the lab-scale, even on practical application. Graphical abstract: Synopsis : In this review, the process of mineral carbonation of BG containing direct and indirect routes is discussed. Additionally, the carbonation kinetics and the synthesis of tunable calcium carbonate (CaCO3 ) are elaborated. Furthermore, the challenge and future work of mineral carbonation of BG for CO2 storage is proposed. Image 1